The 1990 Guide to the Evaluationof Educational Experiences in the Armed Services - American Council of Education (Washington American Council on Education, 1990)
The 1990 Guide to the Evaluationof Educational Experiences in the Armed Services ahs been the standard reference work for recognizing learning acguired in military life. ACE has worked cooperatively with the Department of Defense and the armed services in assisting hundreds of thousands of service men amd women to achieve recognition for their learning.
Keywords: Education